2017
DOI: 10.3897/jhr.54.11290
|View full text |Cite
|
Sign up to set email alerts
|

Notes on the nesting of three species of Megachilinae in the Dubai Desert Conservation Reserve, UAE

Abstract: Some observations on the nesting of three species belonging to phylogenetically interesting lineages of Megachilinae are presented. Published knowledge of the nesting of these species, Megachile (Maximegachile) maxillosa Guérin-Méneville (Megachilini), Megachile (Eurymella) patellimana Spinola (Megachilini), and Pseudoheriades grandiceps Peters (currently assigned to the Osmiini), is fragmentary making the notes presented here a worthwhile addition. The brood cells of M. maxillosa and of P. grandiceps, constru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…Although some studies have found that species nesting in small cavities are more abundant in urban than nearby natural areas (Cane et al, 2 005), ground‐nesting bees are generally more abundant and species rich than cavity‐nesting species in urban areas (Supplementary Materials S1), although slightly less than the estimated global level of 83% (Harmon‐Threatt, 2020). This difference may indicate cavity‐nesting bees can capitalise on the novel substrates present in urban areas (Gess & Roosenschoon, 2017; MacIvor & Moore, 2013; Prendergast, 2019) (Figure 6).…”
Section: Discussionmentioning
confidence: 99%
“…Although some studies have found that species nesting in small cavities are more abundant in urban than nearby natural areas (Cane et al, 2 005), ground‐nesting bees are generally more abundant and species rich than cavity‐nesting species in urban areas (Supplementary Materials S1), although slightly less than the estimated global level of 83% (Harmon‐Threatt, 2020). This difference may indicate cavity‐nesting bees can capitalise on the novel substrates present in urban areas (Gess & Roosenschoon, 2017; MacIvor & Moore, 2013; Prendergast, 2019) (Figure 6).…”
Section: Discussionmentioning
confidence: 99%
“…(MacIvor, ). Recent studies in eastern Canada (MacIvor & Moore, ) and Dubai (Gess & Roosenschoon, ) have found plastic fragments being used in place of large leaf fragments to close individual brood cells. Although these behaviours might be incidental, these findings indirectly suggest that the bees might be limited by the abundance of broadleaf plants in those localities.…”
Section: Conservation Implicationsmentioning
confidence: 99%
“…By incorporating material readily available from the surrounding environment with resin, such material functions as a filler with resin as the binding agent in a resin aggregate. For example, some megachilids living in deserts, such as Pseudoheriades grandiceps Peters (Megachilidae: Osmiini) and Megachile ( Maximegachile ) maxillosa Guérin‐Méneville (Megachilidae: Megachilini), use sand as an aggregate material for mixing with resin (Gess & Roosenschoon, 2017).…”
Section: Resin In Nest Structuresmentioning
confidence: 99%